1992
DOI: 10.1128/jb.174.7.2412-2415.1992
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the gene complementing uvr-402 in Streptococcus pneumoniae: homology with Escherichia coli uvrB and the homologous gene in Micrococcus luteus

Abstract: The repair ability for UV-induced damage observed for Streptococcus pneumoniae proceeds through a system similar to the Uvr-dependent system in Escherichia coli. The DNA sequence of a gene complementing uvr-402, a mutation conferring UV sensitivity, was determined. Alignments of the deduced amino acid sequence revealed an extensive sequence homology of 55% with the UvrB protein of E. coli and 59%o with the UvrB-homologous protein of Micrococcus luteus. Nucleotide-binding site consensus was observed. The high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…2, the amino acid sequence of T. thermophilus UvrB protein is similar to that of other UvrB proteins. Comparison of the T. thermophilus UvrB protein with those of E. coli (19), M. luteus (20), Streptococcus pneumoniae (26), and Neisseria gonorrhoeae (27) revealed identities of 54, 52, 55, and 52% and similarities of 68, 66, 69, and 67%, respectively. The finding of the uvrB gene in T. thermophilus suggests that a UvrABC-like nucleotide excision repair system is present in this extremely thermophilic bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…2, the amino acid sequence of T. thermophilus UvrB protein is similar to that of other UvrB proteins. Comparison of the T. thermophilus UvrB protein with those of E. coli (19), M. luteus (20), Streptococcus pneumoniae (26), and Neisseria gonorrhoeae (27) revealed identities of 54, 52, 55, and 52% and similarities of 68, 66, 69, and 67%, respectively. The finding of the uvrB gene in T. thermophilus suggests that a UvrABC-like nucleotide excision repair system is present in this extremely thermophilic bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…Emission spectra of both UvrB mutants show a blue shift in max , either relative to tryptophan in water (355 nm), or compared with spectra obtained following denaturation of the proteins in a 6 M guanidine hydrochloride buffer (yielding a 356-nm maximum for both mutants; spectra not shown). The shift, generally indicative of a more hydrophobic environment, is greater for Trp 47 (338.5 nm) than for Trp 51 (345 nm). The quantum yield for Trp 47 , 0.15, is slightly greater than that for tryptophan in water, 0.14 (38), and comparable with the difference seen in emission intensity between native and guanidine-denatured UvrB-F47W (12% greater in native buffer).…”
Section: Preparation Of "Tryptophan Reporter" Mutants and Proteins-rementioning
confidence: 90%
“…This suggests that amino acid residue 477 is a histidine (CAC codon) rather than an arginine (CGC). Histidine occupies this position in the UvrB sequences of Micrococcus luteus (46), Streptococcus pneumoniae (47), and Neisseria gonorrheae (48).…”
Section: Preparation Of "Tryptophan Reporter" Mutants and Proteins-rementioning
confidence: 99%
See 1 more Smart Citation
“…It is mediated by the UvrABC excinuclease enzyme complex and the helicase UvrD (43), a system capable of dealing with a broad range of bulky and/or helix-distorting lesions, such as UV-induced photodimers and oxidized thymines, intraand interstrand cross-links, and other large base modifications formed through exposure to DNA-modifying agents (2). Analysis of NER in Bacillus subtilis (43), Streptococcus pneumoniae (47), Mycoplasma genitalium (43), and Deinococcus radiodurans (33) indicated that the repair mechanism originally characterized in E. coli is highly conserved in all prokaryotes. Interestingly, the mycobacterial UvrD1 protein has recently been shown to possess an additional role in DNA metabolism outside of NER; it was shown to physically and functionally interact with Ku, a protein participating in the nonhomologous-end-joining pathway of DNA double-strand break repair.…”
mentioning
confidence: 99%